Improving Sustainability in the Palm Oil Supply Chain: Cradle-to-Gate Economic, Environmental, and Social Life Cycle Evidence from Indonesia - Muhammad Salman Hanan Fadlillah; Silvana Maulidah; Fitria Dina Riana (Postgraduate, University of Mataram, 2026)
The palm oil supply chain plays a strategic role in Indonesia’s economy; however, it faces persistent sustainability challenges related to economic volatility, environmental impacts, and social issues. These challenges necessitate an integrated sustainability assessment across all stages of the supply chain. This study aims to evaluate the sustainability performance of the palm oil agroindustry in North Sumatra, Indonesia, by simultaneously assessing economic, environmental, and social dimensions using a Life Cycle Thinking (LCT) approach. The study applies Life Cycle Costing (LCC) to assess lifecycle costs and financial feasibility, Life Cycle Assessment (LCA) using ReCiPe Midpoint (H) and USEtox methods to evaluate environmental impacts, and Social Life Cycle Assessment (SLCA) to analyze social performance. The assessment scope is cradle to gate, covering plantation activities through Crude Palm Oil (CPO) processing. Primary data were collected from 90 respondents, including workers and local communities, through surveys and interviews. Secondary data were used to compile life cycle inventories and cost structures. The results indicate that fertilization, pest and disease control, and fossil-based electricity consumption at the processing stage are the main contributors to environmental impacts, particularly global warming, eutrophication, and toxicity. Economically, the palm oil supply chain generates positive value added and is financially feasible. Social indicators generally meet minimum regulatory standards. Overall, the ecoefficiency assessment categorizes the system as affordable but not yet environmentally sustainable due to high environmental costs. The novelty of this study lies in the integrated application of LCC, LCA, and SLCA within a single cradle-to-gate framework for the palm oil agroindustry in Indonesia, enabling a comprehensive and simultaneous sustainability evaluation